Problems and Perils of Dual Practice/Belonging - Hábito, Rubén L.F. (Buddhist Christian studies, 2026)
This article addresses three issues that those who profess belonging to more than one religious tradition confront and are called to take stock of. First is the question of doctrinal consistency and integrity: are those who profess dual (or multiple) belonging being inconsistent and/or sacrificing integrity in professing adherence to different religious systems that appear to be incommensurable? Secondly, are they not dividing their loyalties between different traditions and are therefore being unreliable in their profession of loyalty? And thirdly, are they falling into a shallow pick-and-choose-what-you-like kind of spirituality that serves only their own egoic desires or needs? Each person who seeks to engage in earnest spiritual practice in more than one tradition needs to take stock of these questions and find one’s way of being consistent, loyal, and coherent in one’s spiritual life.